Assessment of project potential of stevedoring company - Андриевская, Вера Александровна; Павловская, Людмила Анатольевна (Eastern-European Journal of Enterprise Technologies, 2014)
The problem of assessing the project potential of a stevedoring company is considered in this research. It is proposed to extend the current field of using the project potential as an estimate of the enterprise technological maturity level in terms of implementing the project management methodology, and applying it as characteristic features of the successful implementation of a specific project. Such an approach involves a two-level representation of the project potential: at the enterprise level and at the project level. In this context, a methodological approach is developed to assess the project potential of stevedoring companies. This approach involves the calculation of the project potential as an integral value, the attributes of which characterize the company’s image, quantitative supply of resources, qualitative characteristics of resources and availability of involved resources. The potential project assessment can be used in practice in the selection of promising projects as one of the limiting conditions or as a criterion, complementing the traditional effectiveness indexes.